Os impactos do comércio internacional, da mudança tecnológica e da demanda final na estrutura de emprego no Brasil, 1985-1995 (Economia Aplicada, 2003)
This article examines the impact of trade liberalization, technological change and final demand on employment structure by skill level, in Brazil, in between 1985 and 1995. In the light of the Heckscher-Ohlin model, we decompose the employment change, using input-output and PNAD data. The results show relative change on the employment structure in favor of the skilled workers, caused by trade liberalization and technological change.